Profil Pemecahan Masalah Materi Pecahan Siswa Ditinjau dari Adversity Quotient (AQ) - Deviana, Sri; Ismaimuza, Dasa; Rochaminah, Sutji; Paloloang, Muhammad Fachri B. (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to describe the problem-solving profiles of eighth-grade students in the fraction material at SMPN Model Terpadu Madani, based on adversity quotient. The subjects of this study consist of 3 students selected based on the results of the ARP questionnaire and the recommendation of the mathematics teacher. The results of this study show that: (1) The problem-solving profile of students in the climber category can understand the problem by stating what is unknown and what data is given. However, they are less complete in writing down the known data from the problem, designing a well-structured solution plan, carrying out the plan as initially created, answering correctly, and checking their answer using a different method. (2) The problem-solving profile of students in the camper category can understand the problem by determining what is unknown and identifying the given data, designing a good and complete solution plan, carrying out the plan as initially made, and answering correctly, but they do not check their answer afterward. (3) The problem-solving profile of students in the quitter category can understand the problem by stating what is unknown and what data is given. However, they are less complete in writing down the known data from the problem, designing a good and complete solution plan, failing to implement the plan as initially made, not answering correctly, and not checking their answer afterward. In conclusion, there are 3 categories of students that require different treatment and attention from the teacher. Climber students need more attention in writing down the known data and checking their answer using a different method. Camper students need to be encouraged to check their answer after completing the problem, and quitter students require more intensive guidance in understanding the problem and carrying out the solution plan correctly. Keywords: Profile, Problem Solving, Fractions, Adversity Quotient.